Anthropological and methodological (didactic) aspects of work in contemporary sports - Dragan Milanović; Sanja Šalaj (SportLogia, 2014)
Theoretical and methodological issues, solving of which may give a new impulse to the development of sport and sports achievements, are recently generated by newly established centers for scientific and professional work in sports, like sport science institutes, or institutes for applicative theory and methodology of training. Anthropological and methodological scientific investigation within the framework of the centers should solve issues put forward by sport practice, and vice versa, findings and inferences of scientific research into sport should be as quickly as possible built into actual sport practice. It is the only way in which the gap between science and practice can really be bridged over, or in which these two areas can be associated to benefit top-level sports achievements.